Metabolomics analysis of the effects of chelerythrine on Ustilaginoidea virens - Wei, Qinghui; Zhai, Xihai; Song, Weifeng; Li, Zhiyong; Pan, Yaqing; Li, Baoying; Jiao, Zhanli; Shi, Zhenghao; Yu, Jiangtao (Journal of Pesticide Science, 2024)
Rice false smut (RFS) caused by Ustilaginoidea virens is widely distributed in major rice-producing regions. Previous studies have shown that treating RFS with chelerythrine can decrease the germination of fungus spores by 86.7% and induce fungal cell apoptosis. In the present study, the effects of chelerythrine on the metabolism of U. virens explored using metabolomics and analyses of differentially accumulated metabolites and altered metabolic pathways. The top 15 metabolites in random forest analysis were significantly different between groups. In positive ion mode, purine, phenylalanine metabolism, phenylalanine, tyrosine, tryptophan biosynthesis, pyrimidine metabolism, and nitrogen metabolism were dominant. Alanine, aspartate, glutamate metabolism, and phenylalanine metabolism were enriched in negative ion mode. Differentially expressed genes and altered metabolic pathways of U. virens were effected by chelerythrine. The findings support future research on the prevention and treatment of RFS by chelerythrine and provide a theoretical basis for targeted drug delivery.